2019
DOI: 10.1590/s0100-83582019370100067
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of TBH Herbicide Encapsulated on Ca-ALG Microparticles: Leaching and Phytointoxication Plants

Abstract: The aim of this work was to demonstrate a detailed study of the controlled release of the herbicide Tebuthiuron (TBH) encapsulated in microparticles of calcium alginate (Ca-ALG), to evaluate the phytotoxicity in different concentrations of herbicide (4, 6 and 8 g L-1), and their correlation with the depth of leaching using bioindicator plants. The Ca-ALG microparticles were prepared from the crosslinking of sodium alginate by Ca++ containing varied amounts of TBH supplied in calcium chloride (CaCl2) aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Release studies in diverse soil and media improved the controlled release compared to commercial acetamipirid and acidic soils gave the best results. A detailed study of the controlled release of the herbicide Tebuthiuron encapsulated in microparticles of calcium alginate and its correlation with leaching depth using bioindicator plants was demonstrated [ 61 ]. Rychter [ 62 ] found a herbicidal effect exhibited by the herbicide glyphosate with chitosan nanoformulations and established the slow and sustained release of the active ingredient from the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Release studies in diverse soil and media improved the controlled release compared to commercial acetamipirid and acidic soils gave the best results. A detailed study of the controlled release of the herbicide Tebuthiuron encapsulated in microparticles of calcium alginate and its correlation with leaching depth using bioindicator plants was demonstrated [ 61 ]. Rychter [ 62 ] found a herbicidal effect exhibited by the herbicide glyphosate with chitosan nanoformulations and established the slow and sustained release of the active ingredient from the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Bommayasamy et al (2018) reported that weeds can be effectively controlled by slow release herbicide formulations with reduced doses selectively non-toxic to crops, which remain in the soil for a long period to take care of frequently germinating weeds without leaving any residue at the end of crop season. Leaching of tebuthiuron herbicide encapsulated with calcium alginate microparticle was only to a shallow depth which resulted in minimal contamination of soil (Macedo et al, 2019;Xie et al, 2019). oxadiargyl loaded with biochar.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study showed that the application of herbicide-loaded nanoparticles could be used to reduce the use of herbicides with improved efficacy and environmental safety [ 29 ]. While working with sodium alginate nanoparticles on cucumber plants, leaching of commercial herbicide tebuthiuron in soil was found to be higher (40–50 cm deep), while for nanoformulations, it was lower (20–30 cm), suggesting enhanced uptake by plants and less toxicity to non-target organisms such as fish and other aquatic organisms [ 66 ]. Thus, it can be said that encapsulation reduced the cytotoxicity of commercial mancozeb in the present study.…”
Section: Resultsmentioning
confidence: 99%